1993
DOI: 10.1111/j.1467-629x.1993.tb00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality Biases of Accounting Students: Some Implications for Learning Style Preferences

Abstract: This paper reviews the evidence of a Myers-Briggs personality type bias for accounting students. A survey of a sample of accounting majors in three Australian universities supports the overseas evidence that there appears to be a strong tendency for accounting students to have common preferences on three of the four Myers-Briggs dimensions. The findings of this research suggest that while significant diversity is still evident, there is a bias in the Myers-Briggs personality profiles of accounting students tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…However, the expected proportion of the U.S. population possessing this thinking style is in the 2.67–15.45 percent range (Myers and McCaulley 1985). Empirical studies examining accounting students (e.g., Booth and Winzar 1993; Fisher and Ott 1996; Geary and Rooney 1993) are consistent with the above assertion that accountants strongly favor a linear decision‐making style distinguished by analytical and logical thinking and decision‐making. Therefore, based on the above research we predict that professional accountants would tend to possess a predominantly linear thinking style.…”
Section: Entrepreneurship and Balanced Thinking Stylementioning
confidence: 76%
“…However, the expected proportion of the U.S. population possessing this thinking style is in the 2.67–15.45 percent range (Myers and McCaulley 1985). Empirical studies examining accounting students (e.g., Booth and Winzar 1993; Fisher and Ott 1996; Geary and Rooney 1993) are consistent with the above assertion that accountants strongly favor a linear decision‐making style distinguished by analytical and logical thinking and decision‐making. Therefore, based on the above research we predict that professional accountants would tend to possess a predominantly linear thinking style.…”
Section: Entrepreneurship and Balanced Thinking Stylementioning
confidence: 76%
“…Researchers applying the Myers-Briggs Type Indicator have concluded that accounting students' personality types and learning styles differ from students in other disciplines (Booth & Winzar, 1993;Wolk & Nikolai, 1997;Briggs et al, 2007). Further it has been suggested that accounting students differ from other students in terms of achievement, attitude, goal-orientation, independence, self-discipline etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also reveal that Asians, business administration students in France and Quebec, and female students in Germany, and Canadian accounting students are reflective, while engineering students in Finland, the USA, and Canada, tourism students in the UK and Australia, teacher students in the USA, and accounting students in Australia are active (Savander-Ranne and Kolari 2005;Strother 2003;Lashley and Barron 2006;You and Jia 2008;Barmeyer 2004;Jenkins and Holley 1991). Australian accounting students, for one, prefer concrete experience before abstract conceptualization (Auyeung and Sands 1996) and are described as thinkers (Booth and Winzar 1993) along with German business administration students (Barmeyer 2004), Taiwanese nurses (Li et al 2008), and male German accounting students (Barmeyer 2004). These studies show some differences between cultures, especially between Asian and western cultures.…”
Section: Experiences Of Learning Styles 29mentioning
confidence: 94%